3-methoxycatechol causes vasodilation likely via KV channels: ex vivo, in silico docking and in vivo study - Dias, Patrícia; Salam, Rudy; Moravcová, Monika; Saadat, Saina; Pourová, Jana; Vopršalová, Marie; Jirkovský, Eduard; Tebbens, Jurjen Duintjer; Mladěnka, Přemysl (Vascular pharmacology, 2024)
Substituted catechols include both natural and synthetic compounds found in the environment and foods. Some of them are flavonoid metabolites formed by the gut microbiota which are absorbed afterwards. Our previous findings showed that one of these metabolites, 4-methylcatechol, exerts potent vasorelaxant effects in rats. In the current study, we aimed at testing of its 22 structural congeners in order to find the most potent structure and to investigate the mechanism of action. 3-methoxycatechol (3-MOC), 4-ethylcatechol, 3,5-dichlorocatechol, 4-tert-butylcatechol, 4,5-dichlorocatechol, 3-fluorocatechol, 3-isopropylcatechol, 3-methylcatechol and the parent 4-methylcatechol exhibited high vasodilatory activities on isolated rat aortic rings with EC50s ranging from ∼10 to 24 μM. Some significant sex-differences were found. The most potent compound, 3-MOC, relaxed also resistant mesenteric artery but not porcine coronary artery, and decreased arterial blood pressure in both male and female spontaneously hypertensive rats in vivo without affecting heart rate. It potentiated the vasodilation mediated by cAMP and cGMP, but did not impact L-type Ca2+-channels. By using two inhibitors, activation of voltage-gated potassium channels (KV) was found to be involved in the mechanism of action. This was corroborated by docking analysis of 3-MOC with the KV7.4 channel. None of the most active catechols decreased the viability of the A-10 rat embryonic thoracic aorta smooth muscle cell line. Our findings showed that various catechols can relax vascular smooth muscles and hence could provide templates for developing new antihypertensive vasodilator agents without affecting coronary circulation.
Keywords: Sex Factors; vazodilatace; draslíkové kanály řízené napětím; katecholy; Potassium Channels, Voltage-Gated; Vasorelaxant; Aorta, Thoracic; simulace molekulového dockingu; arteriae mesentericae; Vasodilation; vztahy mezi strukturou a aktivitou; Structure-Activity Relationship; vazodilatancia; Hypertension; Catechol; koronární cévy; Coronary Vessels; Dose-Response Relationship, Drug; Female; Molecular Docking Simulation; K(V) channel; Myocytes, Smooth Muscle; svaly hladké cévní; krysa rodu Rattus; Cyclic GMP; zvířata; sexuální faktory; Catechols; Swine; Phenolic; aorta thoracica; arteriální tlak; ženské pohlaví; myocyty hladké svaloviny; Male; potkani inbrední SHR; hypertenze; Blood vessel; guanosinmonofosfát cyklický; Arterial Pressure; Rats; vztah mezi dávkou a účinkem léčiva; Animals; Vasodilator Agents; mužské pohlaví; Muscle, Smooth, Vascular; Rats, Inbred SHR; Disease Models, Animal; prasata; Mesenteric Arteries; modely nemocí na zvířatech